Peningkatan Penguasaan Materi Elastisitas Dan Hukum Hooke Melalui Penggunaan Modul Fisika Dalam Model Pembelajaran Kooperatif - Rahawarin, Maria Lusi Xena; Sapulete, H.; Barus, Carolina S. A. (Physikos: Journal of Physics and Physics Education, 2024)
This study aims to improve students' mastery of Physics, specifically on the topic of Elasticity and Hooke's Law, through the use of modules within a Cooperative Learning Model. This is in response to the low curiosity and academic achievement of XI MIPA students at SMA Negeri 11 Maluku Tenggara. The study is categorized as a quantitative descriptive research. To assess the extent of students' mastery, this study employs a one-group pretest-posttest design. The sample was selected using purposive sampling, consisting of a single group distributed within one class, totaling 16 students. In its implementation, both test and non-test techniques were used to collect data. For the test technique, a set of test questions was used, including a pretest and a posttest, while for the non-test technique, a Student Worksheet (LKPD) was utilized. The data collected was then processed descriptively, referencing the Minimum Completeness Criteria (KKM). To determine the extent of improvement in students' mastery through the use of Physics Modules within the Cooperative Learning Model, the N-Gain test was conducted. The results of the study indicate a significant improvement in mastery, both during the initial test, the intervention, and the final test. Based on the N-Gain test, there was an increase in students' mastery of the topic of Elasticity and Hooke's Law through the use of modules within the Cooperative Learning Model, with an average N-Gain score of 0.8, categorized as high.